Utilization of Tapertis Educational Technology in Learning Multiplication Concepts in Elementary Schools (International Forum of Researchers and Lecturers, 2025)
This study aims to determine the effectiveness of using the Jarimatika method combined with Tapertis media in improving elementary school students' understanding of multiplication concepts. This study uses a quantitative approach with a pre-experimental intact group comparison type design. The research subjects consisted of 17 fourth-grade students of SDN Candigaron 03 who were divided into two groups, namely the experimental group and the control group. Data collection instruments were in the form of tests (pre-test and post-test) and observation sheets. Experts carried out media validation with an average result of 56.33 (outstanding category). Data analysis used paired sample t-test, t-test, and simple linear regression. The results showed a significant difference between the pre-test and post-test results in both groups. The average post-test score of the experimental group was higher (84.89) than the control group (77.12). The regression test showed that Tapertis media significantly affected understanding of multiplication concepts (p < 0.05). This study concludes that the Jarimatika method, supported by Tapertis media, is effective for use in mathematics learning to improve elementary school students' understanding of multiplication concepts.